Goeppertia siqueirana (Marantaceae), a new species from the Brazilian Atlantic Forest - Saka, Mariana Naomi (Phytotaxa, 2025)
Goeppertia siqueirana, a new species of Marantaceae from the Atlantic Forest of Brazil, is described and illustrated. Comments on its habitat, geographic distribution, ecological observations and a morphological comparison with its close relatives, G. applicata and G. widgrenii, are also provided. Goeppertia siqueirana is preliminary considered ‘Vulnerable’ according to the IUCN Red List categories and criteria.